KEPEMIMPINAN INFORMAL BERBASIS PARTISIPASI MASYARAKAT DALAM MENJAGA KETAHANAN PANGAN LOKAL - Pratidina, Ginung; Zenju, Nandang Saefudin; ., Sukarelawati; Sastrawan, Berry (Jurnal Sosial Humaniora, 2020)
Leadership is the most important factor in the management of groups and organizations, so that appropriate leadership is needed in achieving organizational goals. The Sundanese Indigenous Peoples (Kasepuhan) are unique communities to be investigated because the indigenous leaders in their leadership have success in managing their local food so that they rarely experience food shortages. One contributing factor is informal leadership based on community participation carried out by indigenous leaders. Therefore, this study aims to analyze the informal leadership of indigenous leaders based on community participation in maintaining local food security using descriptive analysis methods. Data were collected using literature study and observation techniques by distributing questionnaires and in-depth interviews, then the data were analyzed using analysis techniques Weight Mean Score (WMS). The results showed that the informal leadership of indigenous leaders based on community participation had a value of 3.22 on a scale of 4. this value is interpreted well. Based on observations and interviews with indigenous Kasepuhan Sinar Resmi Chiefs, two-way communication in conducting deliberations on each issue, because these indigenous communities focus on the culture of planting Sawah and Huma only once a year and starting from planting to harvest are carried out simultaneously, so that what is unique’s the indigenous head as the authority in making decisions when to plant to harvest, its members have high obedience, members Kasepuhan do not dare to plant first if the indigenous head has not started planting. This participation’s the strength of indigenous peoples so that they can maintain local food security in the region until now.